The Material Culture of Multilingualism (Educational Linguistics,, 2018)
This volume provides a unique interface between the material and linguistic aspects of communication, education and language use, and cuts across traditional disciplinary boundaries, drawing on fields as varied as applied linguistics, ethnology, sociology, history and philosophy. Taking texts, images and objects as their starting points, the authors discuss how cultural context is envisioned in particular materialities and in a variety of contexts and localities. The volume, divided into three sections, aims to deal with material culture not only in the daily language practices of the past and the present, but also language teaching in a number of settings. The main thrust of the volume, then, is the exposure of natural ties between language, cognition, identity and the material world. Aimed at undergraduates, postgraduates and scholars in fields as varied as education, applied linguistics, sociolinguistics, semiotics and other related disciplines, this volume documents and analyses a wide range of case studies. It provides a unique take on multilingualism and expands our understanding of how materialities permit us new and unexpected insights into multilingual practices. .